Common and holistic crafts education in Finland - Porko-Hudd Mia; Pöllänen Sinikka; Lindfors Eila (Norway, 2022)
The  questions elaborated  upon  and  discussed  in  thisarticle  emanate  from  all  educational  levels at whicheducation and studies in craftsappearin Finland. The followingquestions permeate the article:What isthe statusof Finland ́seducational craft field at the end of the 2010s?What are the challenges and opportunities for crafts on different educational levels? What seem to be the trends for the future of  Finnish  crafteducation?Education  in  crafts  atall  educational  levels  in  Finland  isdirectly  or indirectly affected by the steering documents for general basic education, which have consisted ofthe National Core Curriculum (NCCBE) since2014 (Finnish National Agency for Education, 2016) and the lesson-hour distribution since2012 (Government Decree, 2012). For the first time, the craft subject in theNCCBEhas beenclearly defined as one subject for all pupils with no division into textile craftsor technical crafts. This has influenced how teaching is organised and implemented. More generally, there is also an ever-increasing need forbasic educationto take into account the demands for lifelong learning,  innovation,  and  the  knowledge  and  skills  to  solve  the  problems  of  the  future.  Questions concerning  the  cooperation  between  teachersand  the  nature  of  holistic  craft-based  projects  with content from the wide range of content in the subjectmust be dealt with and resolved. The effects of the curriculum on teacher education consist of the dilemma of restructuring the education and carryingoutfurther educationof subject teachers within common crafts. At the same time, universities in Finland are  undergoing  constant restructuring  due  to  the  strained  economic  situation  in  public  finance.  The Ministry of Education and Culture (MEC) steersthe development ofuniversities by allocating project funding for the cooperation between educational institutions and stakeholders in society. This has led to new ideas regardingcooperation between the four Finnish universities that provide studies in the science of sloyd education, craft, design,and technology education, and crafts science.